UJI MUTU FISIK GRANUL EKSTRAK ETANOL DAUN KEMANGI (Ocimum americanum L.) DENGAN VARIASI KONSENTRASI EXPLOTAB® - Yulistia Budianti Soemarie; Hayatus Sa'adah; Nurul Fatimah; Tri Marga Ningsih (Jurnal Ilmiah Manuntung, 2017)
Bad breath is usually caused by bacteria and food debris left in the mouth. Development of preparations using herbal ingredients, to overcome the problem of bad breath one of them is with utilization basil leaves (Ocimum americanum L.) which have anti bacterial activity. The method of wet granulation is a single method for use in granulation of large doses of active substances because if using direct induced method will require again the addition of a large number of fillers to make it easier forging, but cause the tablet to be not feasible as it will resulting in an increase in tablet size. The type of research conducted is an experimental study. Object the study was basil leaf extract formulated. This formulation was prepared by wet granulation method with variation Explotab® ss crusher ie 2%, 4%, 6% and 8%. Performed wet granulation on each formulation. Granul evaluated the flow time, mass density test, silent angle and fixed assay test. Based on research result the physical quality of ethanol extract granule of basil leaves (Ocimum americanum L.) with explotab® concentration variation it can be concluded that all the formula fulfill the good quality of granule characteristic, because it meets the requirements of parameters of time flow, rest angle, compressibility and density mass